Objectively measured environmental factors in relation to school travel mode among adolescents: a decision tree analysis - Lena Malnes; Tommy Haugen; Emma Charlott Andersson Nordbø; Andreas Ivarsson; Elin Kolle; Geir Kåre Resaland; Runar Barstad Solberg; Andreas Åvitsland; Sveinung Berntsen (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Understanding the factors that influence school travel mode choice is essential for promoting active travel among adolescents. Currently, there is a lack of research that effectively investigates the interactions between demographic and environmental factors on travel behavior. We aimed to investigate the associations between various demographic and environmental characteristics and the choice of school travel modes—walking, cycling, or motorized transport—among adolescents, across the winter and summer seasons. Methods Data from 1409 Norwegian adolescents, aged 14–15 years, who participated in the School In Motion project were analyzed. Self-reported travel modes and demographic characteristics were collected via questionnaires, while environmental characteristics were determined using Geographic Information Systems (GIS). A decision tree analysis was conducted utilizing the chi-squared automatic interaction detection algorithm to discern patterns in the data. The present study has a cross-sectional design. Results During summer, the predominant travel modes were cycling (39%), walking (37%), and motorized transport (24%). Gender was associated with travel mode choices over short distances (< 1.6 km), with girls favoring walking and boys favoring cycling. For longer commutes, steep inclines were associated with reduced walking and cycling, while higher traffic exposure was associated with increased cycling. During winter, walking (50%) was the most common mode, followed by motorized travel (36%) and cycling (14%). Living near peers was associated with increased walking and cycling among girls. For commutes exceeding 2 km, factors such as available bus transit, more streetlights, the absence of steep hills, and higher urban centrality were linked to increased walking and cycling. Conclusions The findings indicated a complex pattern of demographic and environmental factors influencing active travel, with environmental factors becoming increasingly important as commuting distances increased. These findings highlight the importance of considering the interactions of various factors to effectively promote active travel, especially for adolescents undertaking longer commutes. Trial registration Clinicaltrials.gov ID no: NCT03817047. Registered on: January 25, 2019 (retrospectively registered).